(3WHN GdYUjQs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdTjN GdEeGe (B- (3MSGe GdOjf eaJj GdESdGe GYdehG habce Gddg hEjGfG Cfg jMJGL eSGFd WHN GdYUjQ Edi eYQaI SJI CTjGAs
(3BNQgG (B:s
(3hjMJGL ajg Edi ebOeGJ CTjGA efgG (B: (3Cfg eG jLJeY efg VQH GdCTjGA aj eKdgG jchf CehGdG heG jLJeY efg VQH GdCYOGO aj GdCTjGAs
(3efbhdI Yf fSNI TjN GdESdGe LeGd GdOjf eMehO Hf CMeO GdMUjQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3gOjI GdYGQajf (B1 / 783s
(3GdLhGgQ GdeVjI (B1 / 391s
Keywords: (3Gdabg GdMfHdjs